Perceptions of pharmacy clerkship students and clinical preceptors regarding preceptors’ teaching behaviors at Gondar University in Ethiopia - Melaku, Tadesse; Srikanth, Akshaya; Getaye, Yonas; Admasu, Sewunet; Elkalmi, Ramadan Mohamed Mahmod (Korea Health Personnel Licensing Examination Institute, 2016)
This study aimed to compare the perceptions of pharmacy clerkship students and clinical preceptors of preceptors’ teaching behaviors at Gondar University. A cross-sectional study was conducted among pharmacy clerkship students and preceptors during June 2014 and December 2015. A 52-item structured questionnaire was self-administered to 126 students and 23 preceptors. The responses are presented using descriptive statistics. The Mann-Whitney U test was applied to test the significance of differences between students and preceptors. The response rate was 89.4% for students and 95.6% for preceptors. Statistically significant differences were observed in the responses regarding two of the five communication skills that were examined, six of the 26 clinical skills, and five of the 21 parameters involving feedback. The mean scores of preceptors (2.6/3) and students (1.9/3) regarding instructors’ ability to answer questions were found to be significantly different (P= 0.01). Students and preceptors gave mean scores of 1.9 and 2.8, respectively, to a question regarding preceptors’ application of appropriate up-to-date knowledge to individual patients (P= 0.00). Significant differences were also noted between students and instructors regarding the degree to which preceptors encouraged students to evaluate their own performance (P= 0.01). Discrepancies were noted between students and preceptors regarding preceptors’ teaching behaviors. Preceptors rated their teaching behaviors more highly than students did. Short-term training is warranted for preceptors to improve some aspects of their teaching skills.